THE POLICY OF INDONESIAN GOVERNMENT TOWARDS KAFALA SYSTEM IN SAUDI ARABIA (CASE STUDY: VIOLENCE AGAINST MIGRANT WORKERS) - Septa Sari Mulyaningtyas (HI 16 UMY 065, 2016)
*65 This thesis aims to explain how the policy of Indonesian government to protect Indonesian migrant workers in Saudi Arabia. The thesis conducted by descriptive analysis aimed to gain an overview about the real actions of Indonesian government towards Kafala system in Saudi Arabia which create many problems for TKI. The data’s collecting in this thesis used secondary data, using library materials such as books, journals, articles, and also using downloaded data from several online sites on the internet and other media that relevant to the topic of research. This thesis shows that the existence of Kafala system in GCC include Saudi Arabia caused many problems for Indonesian migrant workers, such as exploitation and sexual abuses. As the respond of that phenomenon Indonesian government who responsible for their citizens in Saudi Arabia makes some actions to protect them. There are two actions which mentioned in this paper, first creating some laws about protection and second is makes bilateral diplomacy between both countries which create bilateral agreement signed in 2014. Keywords: Indonesian government, Kafala System, Indonesian Migrant Workers